Insufflation pressure above 25 mm Hg confers no additional benefit over lower pressure insufflation during posterior retroperitoneoscopic adrenalectomy: a retrospective multi-centre propensity score-matched analysis - Billmann, Franck; Strobel, Oliver; Billeter, Adrian; Thomusch, Oliver; Keck, Tobias; Langan, Ewan Andrew; Pfeiffer, Aylin; Nickel, Felix; Müller, Beat P. (Surgical endoscopy and other interventional techniques, 2021)
Insufflation pressures of or in excess of 25 mm Hg CO2 are routinely used during posterior retroperitoneoscopic adrenalectomy (PRA) in most centres. A critical analysis of the surgical literature provides limited evidence to support this strategy.